2017
DOI: 10.1002/ijc.31219
|View full text |Cite
|
Sign up to set email alerts
|

PD‐1 blockade enhances the antitumor efficacy of GM‐CSF surface‐modified bladder cancer stem cells vaccine

Abstract: Eliminating cancer stem cells (CSCs) is a key issue in eradicating tumor. The streptavidin-granulocyte-macrophage-colony stimulating factor (SA-GM-CSF) surface-modified bladder CSCs vaccine previously developed using our protein-anchor technology could effectively induce specific immune response for eliminating CSCs. However, program death receptor-1 (PD-1)/program death ligand 1 (PD-L1) signaling in tumor microenvironment results in tumor-adaptive immune resistance. Although the CSCs vaccine could increase th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 40 publications
0
31
0
1
Order By: Relevance
“…Shi et al developed urothelial CSC vaccine (streptavidin-granulocyte-macrophage-colony stimulating factor surface-modified bladder CSCs) which effectively induced specific immune response for eliminating bladder CSCs [142]. In the paper, they also showed that the combination therapy of PD-1 blockade and CSC vaccine therapy elevated the population of CD4 + , CD8 + , and CD8 + IFN-γ + cells, which leads to the enhancement of the functions of tumor-specific T lymphocytes and elimination of bladder CSCs [142].…”
Section: Anti-pd-1/pd-l1mentioning
confidence: 99%
“…Shi et al developed urothelial CSC vaccine (streptavidin-granulocyte-macrophage-colony stimulating factor surface-modified bladder CSCs) which effectively induced specific immune response for eliminating bladder CSCs [142]. In the paper, they also showed that the combination therapy of PD-1 blockade and CSC vaccine therapy elevated the population of CD4 + , CD8 + , and CD8 + IFN-γ + cells, which leads to the enhancement of the functions of tumor-specific T lymphocytes and elimination of bladder CSCs [142].…”
Section: Anti-pd-1/pd-l1mentioning
confidence: 99%
“…On the other hand, knockdown of PD‐1/PD‐L1 expression also magnifies the efficacy of traditional therapeutic approaches by reducing the immune resistance of tumor tissues . Wang et al utilized small interfering RNA (siRNA) silencing PD‐L1 pathway to break the self‐protecting mechanism of tumor cells against the host immunity, thus boosting the therapeutic efficacy of photodynamic therapy and inhibiting the growth of both existing and metastatic tumors .…”
Section: Delivery System For Provoking Antitumor Immunitymentioning
confidence: 99%
“…The FCM analysis showed that the amount of mature DCs was significantly higher (6.62 ± 1.28%) in the mice treated with MCSC vaccine than other three groups, including phosphate buffered saline (PBS) group (1.75 ± 0.26%), ethanol‐fixed MCSCs group (2.16 ± 0.12%), and SA‐GM‐CSF group (3.08 ± 0.73%). It was demonstrated that the combined therapy of MCSC vaccine and PD‐1 blockade enhanced specific immune response against MCSCs, and 60% of mice were tumor free on day 45 after immunotherapy . Ali et al fabricated a poly(lactide‐ co ‐glycolide) (PLG) cancer vaccine containing GM‐CSF and CpG‐ODN to coordinate the recruitment and antitumor programming of DCs.…”
Section: Stimulation Of Tumor Antigen Presentationmentioning
confidence: 99%